Langfristige Tendenzen der Einkommensverteilung in Österreich - ein Update: Die Verteilung von Einkommen und Vermögen - Alois Guger; Markus Marterbauer (Austrian Institute of Economic Research (WIFO), 2007)
– Income distribution as it currently is and its long-term development are studied from a variety of data sources. In terms of workers, the study focuses on the wages and salaries of the dependently employed. It finds that the gap between low- and high-wage earners is broad and has further widened in recent years, the consequence mainly of a rise in unemployment and greater flexibility of the labour market (i.a. from the noticeable increase in part-time employment). Both phenomena also play a major role in the fact that women's incomes substantially lag behind those of men. State interference does slightly compensate for the large gap, mostly through the large supply of public services (education, health care, etc.) and social transfers, and much less through the tax system. Recent decades found an increase not just in the inbalance of incomes by the dependently employed, but also between incomes from dependent work and incomes from property and business. The share of wages in the national income has noticeably declined. Distribution is increasingly characterised by a high concentration of wealth. It is in this field that there is a great need to improve the data available for scientific analysis.
Keywords: 330; personelle Einkommensverteilung; Einkommensunterschiede zwischen Männern und Frauen; funktionelle Einkommensverteilung; Lohnquote; Einkommensverteilung; Geschlecht; Lohnquote; Österreich